Problematika Pengelolaan Wakaf Pada Lembaga-Lembaga Pengelolaan Wakaf Di Kota Langsa - Rohana72, Rohana (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This paper focuses on management which highlights the problems and alternative solutions. This thinking departs from an assumption about the potential of waqf in Langsa City which is not managed effectively and efficiently. So that raises a question how the problems faced. Using a phenomenological approach, it was found that the management of waqf in Langsa City is still traditional management for consumer purposes. There are still a number of problems with waqf management institutions in Langsa City, both the Baitul Mal Agency, the Indonesian Waqf Agency (BWI) and the Langsa City Ministry of Religion which manage waqf but are still constrained due to low public understanding, not yet professional waqf nadzir, low quality of sources Human Resources (HR) for managing waqf, managed, still with traditional management and the waqf supervisory system is still weak.